Root system distribution and productivity of sugarcane (Saccharum spp.) fertigated by subsurface drip irrigation - Santos, Deivison; Saad, João Carlos Cury [UNESP]; De Castro Gava, Glauber José (My University, 2014)
This research aimed to assess the relationship between the utilization of a subsurface drip irrigation (SDI) system with productivity and distribution of roots in two cultivars of sugarcane (Saccharum spp.). The work was conducted at county of Jaú, São Paulo, Brazil (22° 17's latitude, 48° 34° longitude and average elevation of 580 m). The experimental design was randomized plots, with eight treatments obtained by the combination of two cultivars RB 86-7515 (C1) and RB 85-5536 (C2), under two conditions irrigated (I) and rainfed (S), during two growing cycles. All treatments were planted in double row, spacing 0.40 m between simple lines and 1.80 m between double lines. In irrigated management, the lateral lines were buried at 0.20 m depth in the middle of the double lines. After each harvest, 24 trenches were dug to capture root system images using the profile method, then the images were analyzed using SAFIRA software, resulting in length, area, and volume of the root system. The productivity of the crop yield (TCH) and sugar (TPH) for irrigated C1 was significantly higher than the rainfed C1, irrigated C2 and rainfed C2, in the first harvest. In the first ratoon there was no significant difference among cultivars, but there was a difference between the irrigated and rainfed. The C1 showed lower values for roots length, area, and volume when compared to C2, but the irrigation management presented a distribution more homogeneous along the profile, with no predominance of roots in the surface layer as in non-irrigated management.
Keywords: Irrigation; Saccharum; Safira; SDI; Sugarcane; Yield